Analysis of the Management Control System in Receiving and Distribution of Zakat At Baznas Kota Medan Office - Natasya Agustia Sari; Uswah Hasanah (Penerbit Merdeka Kreasi, 2023)
This study aims to be able to understand more deeply about information science and knowledge, especially knowing the management control system in receiving and distributing zakat. This type of research is a qualitative research method, the research data is more concerned with the interpretation of the data found in the field. The management of collecting zakat funds carried out by the BAZNAS Office is a management that can be said to be quite good, showing that public awareness to spend their wealth for zakat always increases every year. This explains that the enthusiasm of the people of Medan City in paying zakat is very good and this can be an effective thing to improve welfare and reduce the poverty rate of the people of Medan City. But the management control system in managing zakat funds at BAZNAS is still not good because the leadership does not involve the lower management in preparing the BAZNAS budget and program every year where there is still a discrepancy between revenue and distribution.